2015
DOI: 10.3390/rel6020594
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Care Education of Health Care Professionals

Abstract: Abstract:Nurses and health care professionals should have an active role in meeting the spiritual needs of patients in collaboration with the family and the chaplain. Literature criticizes the impaired holistic care because the spiritual dimension is often overlooked by health care professionals. This could be due to feelings of incompetence due to lack of education on spiritual care; lack of inter-professional education (IPE); work overload; lack of time; different cultures; lack of attention to personal spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 74 publications
3
86
0
16
Order By: Relevance
“…In addition, self-reflection was considered as one of the important strategies in the educational guidelines. The teaching and learning strategies identified in the current study are consistent with those of previous studies that acknowledged drama, role playing, case study and discussion, searching databases and research analysis, self-reflection exercises, journaling, tutorial supervision, oral presentation about spirituality, group dynamics, and film and text analysis (Baldacchino, 2015;Bennett & Thompson, 2015;Caldeira et al, 2016;Mthembu et al, 2016). Additionally, Baldacchino (2015) described conceptual models, which may enhance learning about spirituality and spiritual care, such as Kolb's (1984) experiential learning theory, Gibbs' (1988) theory of reflective learning, and the ASSET model for Actioning Spirituality and Spiritual Care Education and Training in nursing (Narayanasamy, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, self-reflection was considered as one of the important strategies in the educational guidelines. The teaching and learning strategies identified in the current study are consistent with those of previous studies that acknowledged drama, role playing, case study and discussion, searching databases and research analysis, self-reflection exercises, journaling, tutorial supervision, oral presentation about spirituality, group dynamics, and film and text analysis (Baldacchino, 2015;Bennett & Thompson, 2015;Caldeira et al, 2016;Mthembu et al, 2016). Additionally, Baldacchino (2015) described conceptual models, which may enhance learning about spirituality and spiritual care, such as Kolb's (1984) experiential learning theory, Gibbs' (1988) theory of reflective learning, and the ASSET model for Actioning Spirituality and Spiritual Care Education and Training in nursing (Narayanasamy, 1999).…”
Section: Discussionsupporting
confidence: 88%
“…There are concerns about pedagogical approaches for teaching spirituality and spiritual care to health professionals (Baldacchino, 2015;Becker, 2009;Bennett & Thompson, 2015;Caldeira et al, 2016;Cruz, Alshammari, Alotaibi, & Colet, 2017); however, the modified Delphi study identified transformational learning as a useful imperative approach. For example, in discussing the importance of transformational learning, panel participants agreed that students should engage in dialogue about their understanding of spirituality as it incorporates cognitive and affective learning.…”
Section: Discussionmentioning
confidence: 99%
“…While not all patients may self‐identify as spiritual, many express a desire to have spiritual issues addressed at end of life (Puchalski et al., ). Further research will inform educational preparation and clinical guidance, which may offset barriers associated with spiritual care assessment (Baldacchino, ; Cone & Giske, ) and facilitate a primary level of spiritual care delivery (Sinclair & Chochinov, ). Our study aims to provide a foundation for understanding the spiritual care communication strategies used by experienced hospice/palliative care nurses with patients and families at end of life.…”
Section: Introductionmentioning
confidence: 99%
“…This is often the result of insufficient training to assess spiritual needs [16,26,27]. To attend to children, nurses need to understand their developmental stage in faith as well as their cognitive, psychosocial, and moral development.…”
Section: Provision Of Spiritual Carementioning
confidence: 99%